ANALISA DAN PERANCANGAN SISTEM INFORMASI PENGOLAHAN DATA PASIEN PADA BIDAN PRAKTEK SWASTA (BPS) - Meldi Anggara Saputra; Ahmad Rufai (Prosiding Amal Insani Foundation, 2022)
Private Practice Midwives are health service providers who contribute significantly to providing services, especially in improving the welfare of mothers and children. Private Practice Midwives are members of the Indonesian Midwives Association (IBI). This Private Practice Midwife received guidance from Midwife Delima, a program from IBI. BPS Rita Herawati, in the process of processing patient data at BPS, still uses the conventional method of recording patient data transactions into a registration book, so patient health data is difficult to control. To overcome this problem, we need a patient data processing system as a whole, starting from the process of inputting patient data to the process of making patient data reports. The analytical method used is the PIECES method and uses the Logical Model design method, which is illustrated by the Data Flow Diagram (DAD). To obtain the necessary data to prepare this thesis report, use data collection techniques, namely observation, interviews and literature study. In preparing this thesis report, various conclusions can be drawn, such as applying data management with a computer system speeds up the data management process, managing data with a computer system can save work time, managing data is easier and more efficient, the data entry process is faster and neatly arranged, data reporting process can be done at any time if needed.